PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA PUZZLE UNTUK MENINGKATKAN KETERAMPILAN MENULIS SURAT PRIBADI PADA PESERTA DIDIK KELAS V SDN SIMOKERTO VI/139 SURABAYA - Fita Arinda; Sandha Soemantri; Sayyidati Marlinda Yunita (PROCEEDING UMSURABAYA, 2024)
The aim of this research is to determine the improvement of personal letter writing skills in class V students at SDN Simokerto VI/139 Surabaya through the application of the contextual teaching and learning model assisted by puzzle media in Indonesian language lessons. Through this contextual teaching and learning model, it is hoped that students will become more active, directly involved in learning, enthusiastic and enthusiastic about participating in learning activities carried out by the teacher. The approach used in this study is a qualitative approach. Meanwhile, the type of research used in this research is classroom action research. Data collection methods consist of observation, tests and documentation. Data analysis techniques are carried out using quantitative and qualitative data analysis techniques. Quantitative data is obtained from the results of students' formative tests at the end of learning. Qualitative data was obtained from observation data regarding the implementation of learning. The results of the research in cycle I showed that 20 students had completed scores above the KKTP or 69%, while 15. 3% had not yet completed. This result increased in cycle II to 82. 7%. It can be concluded that the contextual teaching and learning model can improve personal letter writing skills in class V students at SDN Simokerto VI/139 Surabaya.